Pengaruh Inovasi dan Kualitas Pelayanan Terhadap Kepuasan Masyarakat di Kantor Camat Alam Barajo Kota Jambi - Fadli Al Ikhsal; Moh. Ihsan; Dessy Elliyana (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2026)
This study aims to determine the effect of service innovation and service quality on public satisfaction at the Alam Barajo District Office, Jambi City. This study used a quantitative method with questionnaires distributed to the public as the primary data source. The collected data were then analyzed to determine the extent to which service innovation and service quality contributed to public satisfaction. The results showed that service innovation had a positive and significant effect on public satisfaction, meaning that the better the innovation, the higher the level of public satisfaction. Furthermore, service quality was also shown to have a positive and significant effect, indicating that aspects such as accuracy, clarity of information, and officer attitudes play an important role in shaping public satisfaction perceptions. These findings confirm that increasing service innovation and improving service quality are strategic steps for the sub-district government in an effort to continuously increase public satisfaction. Thus, these two factors must be the main focus in improving public service governance in the region.